2017
DOI: 10.4103/ortho.ijortho_317_16
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approaches for Total Hip Arthroplasty

Abstract: Total hip arthroplasty (THA) has become one of the most reliable and patient-requested surgical interventions in all medicine. The procedure can be performed using a variety of surgical approaches, but the posterior approach, direct lateral approach, and direct anterior approach are by far the most common across the globe. This article highlights the history and technique for each of these common approaches. A review of outcomes and complications for each approach are also provided. Each approach has its own u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 78 publications
(90 reference statements)
0
44
0
2
Order By: Relevance
“…The DAA for THA has grown in popularity owing to its usage of inter-muscular and inter-nervous plane and the preservation of both the external rotators and the hip abductors 7 22) . Literature shows strong results and advantages, in relation to the dislocation rate and heterotopic ossification, compared with other approaches in both mid to long term 23 24 25 26 27 28) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DAA for THA has grown in popularity owing to its usage of inter-muscular and inter-nervous plane and the preservation of both the external rotators and the hip abductors 7 22) . Literature shows strong results and advantages, in relation to the dislocation rate and heterotopic ossification, compared with other approaches in both mid to long term 23 24 25 26 27 28) .…”
Section: Discussionmentioning
confidence: 99%
“…The approach to the hip joint depends upon the component to be revised as anterolateral, direct lateral, or posterolateral approaches are used for acetabular component revision. In general, surgeons avoid using the anterior approach as it has been suggested that bone grafting and approaching the posterior column is difficult through this approach which forms a major step for cup revisions 7) . In addition, because it is a recent it has been sparingly described and limited experience has led to feigning disinterest among arthroplasty surgeons for revision.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the posterior is the most traditional and popular approach worldwide, 1 ), ( 2 the anterior approach has gained prominence during the second half of the 20th century with the contributions of Smith-Petersen. ( 3 ), ( 4 The number of studies comparing different approaches and techniques for THA has increased in recent years, with a recent study highlighting the controversies over the evidence for clinical outcomes and economic factors favoring the anterior approach. ( 5 However, high-quality evidence evaluating the potential superiority of one method over another is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Two senior consultant surgeons performed over 90% of all the surgeries mentioned in this study. Three different approaches were used: in 58 cases a direct anterior approach [15,16], in five cases a lateral transgluteal approach [17] and once a dorsal approach [18,19]. The surgical approach was chosen in way of a) initial approach, b) the bone defect, which has to be addressed in revision surgery and c) the reachability through the chosen approach.…”
Section: Methodsmentioning
confidence: 99%